Rockwell Hardness Method: Theory, Practice and Evolution : monograph - Moshchenok, Vasyl (Харківський національний автомобільно-дорожній університет, 2026)
This monograph presents a comprehensive and systematic exploration of the Rockwell method as one of the cornerstone tools of modern hardness testing. The book clearly explains the physical and metrological foundations of the method, the loading and unloading stages, the formation of the measured result, and the critical role of the indenter. Special attention is given to state-of-the-art hardness testers from leading global manufacturers, the full classification of Rockwell scales, and the practical use of diamond and ball indenters of different sizes. Dedicated chapters extend the Rockwell approach into the nano- and micro-indentation ranges and introduce new concepts of surface, projection, and volume hardness supported by experimental studies. The monograph concludes with a practical operator’s guide for Rockwell hardness testers, making this book equally valuable for researchers, engineers, students, and instructors.
Keywords: Rockwell method; surface hardness of materials; projection hardness; volume hardness; hardness scales; Rockwell hardness testers; microhardness with a spheroconical indenter